Malawi : Seventh and Eighth Reviews Under the Extended Credit Facility Arrangement and Request for Waivers for NonObservance of Performance Criteria, Extension of the Arrangement, Augmentation of Access, Modification of Performance Criterion, and Rephasing of Disbursements-Press Release; Staff Report; and Statement by the Executive Director for Malawi. (IMF Staff Country Reports; Country Report ;, 2016)
This paper provides a review of the economic performance of Malawi under the program supported by an Extended Credit Facility (ECF) arrangement. Malawi's economy has been hit hard by weather-related shocks for a second consecutive year, further weakening growth and worsening food insecurity. Growth is estimated to have declined from 5.7 percent in 2014 to 3 percent in 2015 and is projected to drop further to 2.7 percent this year. Under the ECF program, the macroeconomic framework in the near term will be anchored on a policy mix incorporating a tight monetary stance and a level of domestic fiscal financing consistent with disinflation.